Combination of flow and micropattern alignment affecting flow-resistant endothelial cell adhesion. (October 2017) - Gong, Xianghui; Yao, Jie; He, Hongping; Zhao, Xixi; Liu, Xiaoyi; Zhao, Feng; Sun, Yan; Fan, Yubo
Abstract: Assuring cell adhesion to an underlying biomaterial surface under blood flow is vital to functional vascular grafts design. In vivo endothelial cells (ECs) are located under the microenvironment of both surface topography of the basement membrane and the mechanical loading resulting from blood flow. Both topographical and mechanical factors should thus be considered when designing vascular grafts to enhance the flow-resistant EC adhesion. This study aims to investigate effects of integrating biomaterial surface topography and flow on EC adhesion, which was a deficit in previous studies. Human umbilical vein endothelial cells (HUVECs) were cultured on different fibronectin (FN) micropatterns parallel or perpendicular to the flow direction and exposed to sustained flow with physiological levels of shear stress (15 dyne/cm 2 ). We demonstrated that micropattern alignment parallel to the flow direction enhanced flow-resistant EC adhesion, while micropattern alignment perpendicular to the flow direction attenuated it. Experimental and numeric modeling analysis underlined that the flow-induced mechanic distribution on the surface of cells that were aligned on the micropatterned surfaces and the subsequent cytoskeleton rearrangement were responsible for the significant difference in EC adhesion. Furthermore, pressure on the surface of cells that were aligned on the micropatterned surfaces induced by flow provided a more critical role in EC adhesion than shear stress. These findings highlight the importance of proper combination of topographical and flow cues in enhancement of EC adhesion and may suggest new strategies for designing functional vascular grafts.